Impact of COVID-19 Pandemic on Small and Medium-Sized Enterprises in Kosovo: Array - Çollaku, Besmir; Florim Veliu; Driton Bala (Acta Universitatis Danubius. Œconomica, 2021)
The pandemic situation caused by coronavirus disease (COVID-19) has affected the global and Kosovo economy. Because of restricted measures to prevent the spread of viruses, SMEs have faced worsening financial results. The article aims to assess the impact of the COVID-19 outbreak on these businesses and provide policy recommendations to help SMEs reduce business losses and survive through the crisis. We adopted an explanatory methodology for comprehensively reviewing the available literature, including policy documents, research papers, and reports in the relevant field. Further, to add empirical evidence, we collected data from 70 Kosovo’ SMEs by administrating an online questionnaire. Most of the participating enterprises have been directly affected and surface several issues, such as worsening financial results, decreasing demand, supply chain disruption, and liquidity problems. Based on the regression results, the financial results are affected by a decrease in turnover, but the drop in output and liquidity obstacles are not statistically significant. The findings of our study are consistent with previous studies. We recommend different policies to ease the adverse effects of the outbreak on SMEs. Although our suggested policy recommendations may not be sufficient to help SMEs go through the ongoing crisis, these measures will help weather the storm.